The Laser for Improvement Silicon Solar Cell Efficiency - Al-Taa'y, Wasan Ali (Al-Nahrain Journal of Science, 2011)
The purpose of this study is to improve the efficiency of solar cells composed of silicon single crystal. The silicon crystal was subjected to pulsed laser of wave length (1.06 μm) type Nd –Glass under the condition of darkness and illumination. Electrical properties (I-V) of the irradiated solar cells were studied. The results revealed that the efficiency of some cells is increased after directly irradiated till arrival to steady state. On the other hand some of other cells suffer’s reducing in its efficiency after irradiated till arrival to steady state.